By Using Taguchi And Anova Methods For Optimization of Stress and Deformation For Lap Joint - Neeraj Upadhyay (AG Volumes, 2021)
In several industries, welding is significantly used; aviation industry, automotive industry and construction industry are some of the industries which widely use welding. Therefore, for the welding characteristics or responses, optimization of mechanical properties is considered important. For the factorial design of the experiment, Taguchi method is used that is an appropriate statistical method. Moreover, there are several standard methods for evaluating tensile strength of the material, it’s necessary to develop new ideas for obtaining tensile strength of welding joints. In this present study, the effective way is used to evaluate and optimise the welding techniques with better tensile strength for Lap Joint. The method opts for analysis of Lap welding joint is Taguchi method. Taguchi method is used for the purpose of result optimization. ANOVA method is used for proper judgement of result along with Taguchi method. The stress and deformation is calculated on the ANSYS software.